Mechanisms of endotoxin tolerance in patients with alcoholic liver cirrhosis: role of interleukin 10, interleukin 1 receptor antagonist, and soluble tumour necrosis factor receptors as well as effector cell desensitisation. Issue 2 (1st August 2000) - von Baehr, V; Döcke, W-D; Plauth, M; Liebenthal, C; Küpferling, S; Lochs, H; Baumgarten, R; Volk, H-D
Abstract : BACKGROUND: In patients with alcoholic liver cirrhosis, endotoxaemia is a frequent finding. Unknown mechanisms, however, prevent typical clinical symptoms of endotoxaemia in many patients. METHODS: We determined plasma levels of pro- and anti-inflammatory mediators, ex vivo cytokine secretion capacity, and expression of tumour necrosis factor (TNF) receptors on phagocytic blood cells in 49 patients with alcoholic cirrhosis and 41 age matched healthy controls. RESULTS: In addition to increased levels of proinflammatory cytokines in cirrhotic patients, we observed consistent upregulation of the anti-inflammatory mediators interleukin 10 (IL-10) (plasma 15.75 (1.6) v 6.6 (1.3) pg/ml (p<0.001); ex-vivo 108.4 (22.0) v 40.1 (7.4) pg/ml (p<0.05)), interleukin 1 receptor antagonist (plasma 527.1 (83) v 331.4 (56) pg/ml (p<0.05); ex vivo 19.9 (3.4) v 10.2 (2.7) ng/ml (p<0.01)), and soluble TNF receptors (sTNF-R) in plasma (sTNF-RI 3157.2 (506.2) v 607.9 (300.3) pg/ml; sTNF-RII 3331.0 (506.2) v 1066.4 (225.1) pg/ml (p<0.001 for both)). Desensitisation at the target cell level was indicated by reduced expression of TNF receptor I on granulocytes (64.8 (6.5) v 40.1 (7.3)% positive cells; p<0.05) and unaltered plasma levels of soluble E-selectin. CONCLUSION: In patients with alcoholic liver cirrhosis, upregulation of the pro- and anti-inflammatory cytokine system and simultaneous desensitisation of effector cells could explain the restricted systemic inflammatory response to chronic endotoxaemia. This alteration in immune status may lead to impairment of host defences against infections which are frequent complications of alcoholic cirrhosis.